Analysis of environmental health and sustainability of Brazilian municipalities in the Baixo Pardo/Grande River Basin - Alvares, Maria Eugênia Gonçalez; Ventura, Katia Sakihama (Revista Nacional de Gerenciamento de Cidades, 2024)
Population growth, the lack of urban planning and poor sanitation infrastructure have persisted in the management of urban space when the core issue is environmental health and the sustainability of municipalities. This paper aimed to evaluate the environmental health and sustainability of the 12 Brazilian municipalities in the Baixo Pardo/Grande (SP) river basin. The exploratory approach and the case study guided the comparative analysis of sustainability through the Sustainable Cities Development Index (100 indicators) and the Brazilian Environmental Health Index (18 indicators) to obtain an integrated classification of these indices on a municipal scale. The analyses highlighted that 100% of studied municipalities reached medium level (score: 51-75) out for health and sustainability, especially to Altair and Orlândia results Bebedouro, Viradouro and Colina require careful monitoring of the following indicators sanitary sewage and vector control, water and socioeconomic resources, and water and socioeconomic resources, respectively. The basic sanitation, health diseases and infant mortality pillars relating to these indices identified seven similar indicators, that is, they measure the same aspects of the analyzes. Then, they were excluded to avoid duplication of data. The least promising results of Sustainable Development Goals (SDGs) were Gender equality (SDG 5), Industry, innovation and infrastructure (SDG 9), Protect life on Earth (SDG 15) and Partnerships and means of implementation (SDG 17). Finally, the great challenges of the Baixo Pardo Grande River Basin pointed out social, technological and connectivity issues between interinstitutional sectors from a regional perspective.